Bibliometric Analysis: Higher Education Funding in Asia: Penelitian - Syahida Norviana; D. Harsya Widyatama; Djoko Suryo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Higher education institutions in Asia play a pivotal role in the promotion of sustainable development. However, the complex funding challenges that are currently being faced represent a significant impediment to the establishment of a fair and high-quality education system. The present study has been designed to map the development of literature on higher education funding in Asia, with a view to identifying trends, research focuses, and inter-country collaboration networks. The present study obtained research data from 146 Scopus-indexed articles published between 2004 and 2025. The analysis was conducted using VOSViewer software to identify dominant keywords, the most productive authors, and collaborative relationships between institutions and countries. The results indicate that the primary subjects addressed encompass regional disparities, performance-based funding mechanisms, and public fund governance issues. As a general rule, the extant literature highlights the necessity for more contextual and transparent funding models. The present study demonstrates that governments and educational institutions in Asia must enhance governance, expand cross-sector collaboration, and formulate funding policies in accordance with the principles of Sustainable Development Goal 4 (SDG 4) if inclusive and sustainable higher education is to be achieved.